2023
DOI: 10.1038/s41598-023-40160-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking as a tool for the discovery of molecular targets of nutraceuticals in diseases management

P. C. Agu,
C. A. Afiukwa,
O. U. Orji
et al.

Abstract: Molecular docking is a computational technique that predicts the binding affinity of ligands to receptor proteins. Although it has potential uses in nutraceutical research, it has developed into a formidable tool for drug development. Bioactive substances called nutraceuticals are present in food sources and can be used in the management of diseases. Finding their molecular targets can help in the creation of disease-specific new therapies. The purpose of this review was to explore molecular docking's applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(66 citation statements)
references
References 114 publications
0
64
0
2
Order By: Relevance
“…Molecular docking represents a structure‐based drug design method that gained its popularity due to ease of access and low computational cost, which, however, comes at the cost of lower accuracy 77,78 . Its two principal steps include the prediction of the ligand conformation within the active site cavity (binding pose) and the evaluation of pose quality by calculation of the free binding energy (docking score) 79,80 . Throughout the years, molecular docking has been successfully used for high‐throughput virtual screenings of small ligands, 81 docking of protein–protein pairs, 82 modeling ligand‐DNA intercalations, 83 and assisting X‐ray crystallography in the fitting of substrates and inhibitors to electron density 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking represents a structure‐based drug design method that gained its popularity due to ease of access and low computational cost, which, however, comes at the cost of lower accuracy 77,78 . Its two principal steps include the prediction of the ligand conformation within the active site cavity (binding pose) and the evaluation of pose quality by calculation of the free binding energy (docking score) 79,80 . Throughout the years, molecular docking has been successfully used for high‐throughput virtual screenings of small ligands, 81 docking of protein–protein pairs, 82 modeling ligand‐DNA intercalations, 83 and assisting X‐ray crystallography in the fitting of substrates and inhibitors to electron density 79 .…”
Section: Resultsmentioning
confidence: 99%
“…To comprehensively evaluate the predictive accuracy of models constructed with different features and apply them to the development of novel N-HSP90α inhibitors, we employed a strategy that combines docking-based affinity screening with binding kinetics screening to identify potential small molecule inhibitors. Molecular docking is a computational technique to predict the binding mode and binding affinity of ligand and receptor proteins, which is widely used in drug discovery and design. The screening process is succinctly outlined in Figure . Initially, structures of N-HSP90α residues 104–114 with four distinct conformations (PDB IDs: 5J2X, 1YC1, 2XHX, and 5LQ9) were optimized using the Protein Preparation module in the Maestro software (Schrödinger, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…230 For instance, molecular docking and binding mode analysis have shown that these methods can make small molecules that are more active than those in the crystal structure and have similar places where they can interact with ligands. 232 Pharmaceutical chemists may obtain novel concepts and recommendations from this, which could expedite the process of developing innovative inhibitors and drugs. 233 The ligand-based drug design covering library preparation, compound representation, and SAR analysis to molecular generation is discussed in Figure 3.…”
Section: Dl-based Molecular Generation Techniques Using Molecular Gen...mentioning
confidence: 99%
“…These DL-based molecular generation techniques can also help identify protein-active sites . For instance, molecular docking and binding mode analysis have shown that these methods can make small molecules that are more active than those in the crystal structure and have similar places where they can interact with ligands . Pharmaceutical chemists may obtain novel concepts and recommendations from this, which could expedite the process of developing innovative inhibitors and drugs .…”
Section: Rational Drug Design Technologiesmentioning
confidence: 99%